Developing students’ geographical culture through the integration of tourism in geography education in Kazakhstan - Oralkul, Gulaiym; Amangeldi, Ozerke; Tokayeva, Lyayli; Duisebayeva, Kulzada; Nurbaeva, Aray (International Journal of Innovative Research and Scientific Studies, 2025)
This study explores the role of integrated tourism education in promoting geographic culture among students in Kazakhstan. It examines the combination of theoretical knowledge with practical tourism activities and modern educational technologies, including GIS, Augmented Reality (AR), and Virtual Reality (VR). The research involved 119 geography teachers and 172 students (aged 15-18) from two schools in Almaty. Methods included curriculum analysis, pedagogical experiments, surveys, and observations. The results show that integrated learning, especially ICT-based approaches, improved students’ spatial thinking and geographical awareness by 40% compared to traditional methods. Teachers recognized the benefits of digital tools in geography education, but 65% reported that challenges such as limited internet access and a lack of interactive whiteboards hindered implementation. The study concludes that the integration of geography, tourism, and digital technologies is crucial for the development of students’ geographical culture. However, addressing technical infrastructure issues and providing comprehensive teacher training in digital tools is essential for effective implementation.